2021
DOI: 10.1093/cz/zoab082
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of eyespots and masquerade in protecting artificial prey across ontogenetic and seasonal shifts

Abstract: When constraints on antipredator coloration shift over the course of development, it can be advantageous for animals to adopt different color strategies for each life stage. Many caterpillars in the genus Papilio exhibit unique ontogenetic color sequences: e.g., early instars that masquerade as bird feces, with later instars possessing eyespots. I hypothesize that larvae abandon feces masquerade in lieu of eyespots due to ontogenetic changes in signaler size. This ontogenetic pattern also occurs within broader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…One possibility is that the size of the model may favour attacks by birds. It has been observed that birds respond positively to increased prey size (Postema 2021), having a strong impact at the end of the larval period; whilst, the effect is the opposite in arthropods since these mainly attack small individuals (Feeny et al 1985, Lövei & Ferrante 2017, Remmel & Tammaru 2009, Remmel et al 2011). Barton (1986) observed that ants attack eggs and small larvae of P. sennae , while avoiding lepidopteran larvae larger than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the size of the model may favour attacks by birds. It has been observed that birds respond positively to increased prey size (Postema 2021), having a strong impact at the end of the larval period; whilst, the effect is the opposite in arthropods since these mainly attack small individuals (Feeny et al 1985, Lövei & Ferrante 2017, Remmel & Tammaru 2009, Remmel et al 2011). Barton (1986) observed that ants attack eggs and small larvae of P. sennae , while avoiding lepidopteran larvae larger than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with those reported by Ferrante et al (2022) and Sam et al (2015) in other experiments using artificial larvae. Despite that, the general trend is for arthropods to be the main predators (Ferrante et al 2014, 2017a, 2021, Magagnoli et al 2018, Molleman et al 2016, Pena et al 2021. The fact that the most common markings found on models fitted those of birds does not mean that these are the main predators in urban environments.…”
Section: Potential Predatorsmentioning
confidence: 99%
“…Field learning experiments present artificial prey to all potential predators in the community instead of targeting specific predator individuals or species (e.g., refs. [67][68][69][70][71][72][73][74]. Final attack probabilities, forgetting rates, and the strength of generalization can be derived from attack rates in the same way as the laboratory experiments.…”
Section: Testing the Unforgetful Predator Hypothesis In Natural Commu...mentioning
confidence: 99%
“…This effect would fulfill the definition of a "momentary, transient signal" that startles a predator enough to slow or halt its attack (Umbers & Mappes 2016). Additionally, leaf rolls may offset potential detectability costs of large, conspicuous eyespots , Postema 2022. While the startling "conceal-then-reveal" effect of eyespots within leaf rolls has been presumed for both P. troilus larvae and other lepidopteran species (Wagner 2005;Janzen et al 2010), this assumption remains untested.…”
Section: Introductionmentioning
confidence: 99%